Climate Change in Indonesia: Green Steel - Nicholas Standish (MBI, 2025)
Most studies of Indonesian Green House Gas (GHG) emission deal with land, forestry, electricity and construction, and exclude iron and steelmaking as such, which emits a sizeable 2.75t CO2equivalent/ton of steel. This paper focuses on GHG emissions of Indonesian iron and steel industry, now existing and under construction - and that projected to 2060. It gives actual steps of how to start reducing the industry’s GHG immediately using charcoal and employ ordinary people in environmental plantations and help poor people in towns and villages to earn some money by buying wood cuttings from them and processing it in distillation plants. It considers Indonesian ways and culture. There is no modelling of any process and activity, so everything can be checked from first principles or by reference to the source.One contentious conclusion is that to reduce the steel industry’s GHG to near zero, it is imperative to use nuclear energy. Its use in Indonesia has been committed to by President Prabowo at the G20 Summit in Brazil in November 2024 and its actual start with 28 reactors was announced the following month (December 2024). This elicited immediate protests with a slogan of: “Indonesia bukan Chernobyl”. A useful response by the government could be: Kami sangat setuju. Kami juga orang Indonesia. Sebab itu kita akan membangun reaktor gas Mitsubishi karena sama sekali reaktor tsb tidak mungkin meleleh seperti reaktor Chernobyl.